2017
DOI: 10.2174/1567205014666170908094931
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review Investigating Multi-disciplinary Team Approaches to Screening and Early Diagnosis of Dementia in Primary Care – What are the Positive and Negative Effects and Who Should Deliver It?

Abstract: Early diagnostic and screening programmes have not been widely adopted into primary care. Until there is rigorous evidence assessing the clinical and cost-effectiveness of such programmes, there remains insufficient evidence to support the adoption of these programmes in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(167 reference statements)
0
18
0
Order By: Relevance
“…Consistent with this finding, a qualitative study showed that self-perceived susceptibility to illness may affect ones acceptance of dementia screening. 21 Therefore, people who feel poor health status may be more 25 To solve this issue, it recommends that screening by primary care physicians with quick referral to specialists to confirm the possibility of early dementia for initiation of treatment is recommended. 26 The Japanese government established a training system for physicians certified as Dementia Support Doctors (DSD); the DSD supports older people with dementia from the early stages and provide primary care doctors and care workers with necessary education.…”
Section: Factors Associated With Willingness To Use Subsidized Systemmentioning
confidence: 99%
“…Consistent with this finding, a qualitative study showed that self-perceived susceptibility to illness may affect ones acceptance of dementia screening. 21 Therefore, people who feel poor health status may be more 25 To solve this issue, it recommends that screening by primary care physicians with quick referral to specialists to confirm the possibility of early dementia for initiation of treatment is recommended. 26 The Japanese government established a training system for physicians certified as Dementia Support Doctors (DSD); the DSD supports older people with dementia from the early stages and provide primary care doctors and care workers with necessary education.…”
Section: Factors Associated With Willingness To Use Subsidized Systemmentioning
confidence: 99%
“…The study by Vandentorren et al (pp. 207–214) following the Paris terrorist attacks shows that 11%, 18% and 31% of civilians developed symptoms of depression, post-traumatic stress disorder and anxiety, respectively, after 6 months; symptom levels were much lower among rescue workers, although longer-term follow-up may show greater health problems 6 8 …”
Section: Big Data and Clinical Epidemiologymentioning
confidence: 99%
“…What might the plight have been of people with dementia, a condition now known to affect 50 million people globally at a cost of $1 trillion? 9 More people are being diagnosed with dementia in the UK, and care standards are improving 10 . More research is now needed, not only on biological–cellular and lifestyle-focused prevention, but also on care processes and support for patients, with implications for all health professionals and teams in primary and secondary care 6 , 11 . Doctors appear to struggle with the delivery of a dementia diagnosis in memory clinics and vary from being sensitive-suggestive to abrupt, the latter surprisingly being more prominent with those with more significant impairments (Dooley et al , pp.…”
Section: Language Mattersmentioning
confidence: 99%
“…GPs report barriers to making a dementia diagnosis. They may resist undertaking a cognitive assessment because of concerns about conferring stigma related to dementia (Gove, Downs, Vernooij-Dassen, & Small, 2016); or due to uncertainty about how useful an early diagnosis can be if interventions and support are absent (Fox, Lafortune, Boustani & Brayne, 2013;Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 99%